Analiza dobrych praktyk ekonomii społecznej w Polsce – o zasobach i ich pozyskiwaniu w przedsiębiorczości społecznej - Marzena Starnawska (Studia i Materiały)
The aim of this paper is to analyse and identify resources, resourcing ways and challenges related among “good practice” examples presented in “Atlas of social economy in Poland”. The Atlas has been promoted in the biggest Internet portal on social enterprise, social economy and social entrepreneurship in Poland. To achieve this aim, the author uses 25 cases of “good practices” presented in the Atlas and deconstructs the profiles’ content. Two types of social enterprise initiatives, as regards resource mobilization are identified. Also, related challenges are discussed in the context of resource mobilization.